Emotional Exhaustion of Public Employees: Dominant Effect Between Job Insecurity and Justice - Boni Saputra; Hidayatul Fajri; Deni Triyanto; Dedi Kusuma Habibie (Jurnal Ilmu Administrasi: Media Pengembangan Ilmu dan Praktek Administrasi, 2021)
The purpose of this study was to analyze the effect of job insecurity and organizational justice on employees' emotional exhaustion. This conceptual research wants to prove the presence or absence of significant influence caused by the independent variable on the dependent variable either partially or simultaneously. The study was conducted at the Government Bureau of the Regional Secretariat of West Sumatra Province. The research method uses an associative quantitative approach with employee research subjects. This study involved 37 respondents with a Nonprobability Sampling technique. The type of data used is primary data and secondary data. Data collection uses a Likert scale questionnaire. Previous questionnaires have been tested for validity and reliability. Data were analyzed using multiple linear regression analysis (multiple regression) which was tested for its classic assumptions. Hypothesis test results provide evidence of a significant influence between the independent variables on the dependent variable either partially or simultaneously. The results showed that there was a significant influence of the variable job insecurity on emotional exhaustion by 49.4%; there is a significant influence of organizational justice variables on emotional exhaustion of 56.2%, in addition, this study also proves that there is a significant simultaneous effect on job insecurity and organizational justice variablesÂ  on emotional exhaustion with a contribution of 62.8%.